(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
The purpose of this study was to find out how English adjective clauses are translated into Indonesian and to identify the suitable theories and strategies that can be applied to analyze the adjective clauses. This research is limited to the analysis of the translation of adjective clauses with relative pronouns; that, which, who, and adjective clauses with relative adverb where, using semantic and syntactic strategies by Chesterman and theories related to them. The method applied was descriptive qualitative research by collecting and analyzing both English and Indonesian versions of the novel. The results obtained after I analyze the 20 data out of 100 data are; the adjective clauses with relative pronoun that (7), the adjective clauses with relative pronoun which (2), the adjective clauses with relative pronoun who (7), and the adjective clauses with relative adverb where (4). Furthermore, the synonymy strategy and theory are often used by the novel translators in translating the adjective clause.